Incidence and progression of diabetic retinopathy: a systematic review. Issue 2 (February 2019) - Sabanayagam, Charumathi; Banu, Riswana; Chee, Miao Li; Lee, Ryan; Wang, Ya Xing; Tan, Gavin; Jonas, Jost B; Lamoureux, Ecosse L; Cheng, Ching-Yu; Klein, Barbara E K; Mitchell, Paul; Klein, Ronald; et al.
Summary: Diabetic retinopathy is a leading cause of vision impairment and blindness. We systematically reviewed studies published from Jan 1, 1980, to Jan 7, 2018, assessed the methodological quality, and described variations in incidence of diabetic retinopathy by region with a focus on population-based studies that were conducted after 2000 (n=8, including two unpublished studies). Of these eight studies, five were from Asia, and one each from the North America, Caribbean, and sub-Saharan Africa. The annual incidence of diabetic retinopathy ranged from 2·2% to 12·7% and progression from 3·4% to 12·3%. Progression to proliferative diabetic retinopathy was higher in individuals with mild disease compared with those with no disease at baseline. Our Review suggests that more high-quality population-based studies capturing data on the incidence and progression of diabetic retinopathy with stratification by age and sex are needed to consolidate the evidence base. Our data is useful for conceptualisation and development of major public health strategies such as screening programmes for diabetic retinopathy.